Quantitative Evaluation of The Factors for Improving The Quality Of Education In Higher Educational Institutions (Eurasian Journal of Learning and Academic Teaching, 2023)
Analysis of variance is a powerful modern statistical method for processing and analyzing experimental data in the humanities. This is very closely related to the specific methodology for planning and conducting experimental studies. The article describes a quantitative assessment of the factors for improving the efficiency of personnel in higher education institutions. The author proposes mathematical models of socio-economic factors that affect the effectiveness of teachers. The analysis of variance also revealed the influence of a number of factors on the main socio-economic indicators of higher educational institutions.